Sterilization and low temperature effects on regenerative potential of hyaluronic acid - Gurina, Tetiana; Nardid, Eduard; Seliuta, Anatolii; Polyakova, Anna; Martsenyuk, Valentyna (Problems of Cryobiology and Cryomedicine, 2025)
Due to its physical properties and pharmacological activity, hyaluronic acid (HA) has considerable potential for use in cryobiology and cryomedicine. The aim of the study was to create a method for sterilizing aqueous solutions of HA that does not reduce its regenerative properties, and to study the effect of low temperatures on their preservation. For the sterilization of aqueous solutions of HA, a gentle sterilization regimen — tyndallization — was proposed, which at the same time ensures the sterility of the solutions and does not affect their regenerative properties. The effects of tyndallization and low temperatures on the preservation of the regenerative properties of 1 and 2% aqueous solutions of HA of different molecular weights: low molecular weight (LMW HA) (<100 kDa) and high molecular weight (HMW HA) (>2000 kDa) was studied in an animal model of excision wound healing. It has been shown that low temperatures do not change the regenerative properties of HMW HA and LMW HA (even in the thermocycling mode), which opens up wide possibilities for use in cryobiology and cryomedicine. Probl Cryobiol Cryomed 2025; 35(2):68–75